Effectiveness of two pots and others factors for harvesting hard blue crabs callinectes sapidus in Lake Maracaibo, Venezuela - Ferrer Montaño, Orlando José (Ciencia, 1970)
The blue crab Callinectes sapidus Rathbun supports important fisheries along Lake Maracaibo, Venezuela. The 1993 catch was 4211 MT, worth slightly more than $2 million to the fishermen. Blue crab is one of the most important fishery resources exploited by artisanal fishermen. However, little is known concerning its biology and fishery. From 1990, restrictions have been imposed on its fishery but not under scientific criteria. This study, initiated in 1993 to evaluate the effects of fishing methods and to formulate procedures for an effective management strategy for blue crab in Me Maracaibo, presents results on selectivity of gears. The study was conducted three days monthly for a total of 19 samples using two type of pots: Commercial pot (CP. 2x1 inches mesh size, 35 pots), and experimental pot (EP, 1x1 inches mesh size, 10 pois). Pots were set along the sandy and muddy edges of the lake in depths ranging from 1.5 to 18 m. Sexual composition did not differ significantly among gears (P>0.05) and was about 11% females and 89% males year-round. The abundance of blue crabs in pots fluctuated seasonally. EP produced 1.642 crabs/trap.d, which was 2.2 times higher than CP. The size structure of blue crabs sampled over the sampling period was similar for both gears (P0.05). CP now in use do not take crabs larger than those designed as EP. EP are eventually used by crabbers when catches are lows. However, this gear has been prohibited because this type of gear does not allow an effective renewal of the crab fishing stock.